2014
DOI: 10.1093/glycob/cwu021
|View full text |Cite
|
Sign up to set email alerts
|

Gene expression levels of  4-galactosyltransferase 5 correlate with the tumorigenic potentials of B16-F10 mouse melanoma cells

Abstract: Our previous studies showed that mouse β4-galactosyltransferase 5 (β4GalT5) is a lactosylceramide (Lac-Cer) synthase, and that its gene expression increases by 2- to 3-fold upon malignant transformation of cells. In the present study, we examined whether or not the tumorigenic and metastatic potentials of B16-F10 mouse melanoma cells can be suppressed by reducing the expression of the β4GalT5 gene. We isolated a stable clone named E5 whose β4GalT5 gene expression level was reduced to 35% that of a control clon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
28
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(29 citation statements)
references
References 48 publications
1
28
0
Order By: Relevance
“…16,17) After being cultured for 72 h, the plasmid-transfected cells were selected with DMEM containing 10% FCS and hygromycin B (500 µg/mL) for two weeks.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…16,17) After being cultured for 72 h, the plasmid-transfected cells were selected with DMEM containing 10% FCS and hygromycin B (500 µg/mL) for two weeks.…”
Section: Methodsmentioning
confidence: 99%
“…Our previous studies demonstrated that the malignant properties of cancer cells are suppressed by regulation of the expression levels of the β4GalT genes, 16,17) indicating that the changes of cell surface glycosylation contribute to the suppression of malignant properties of cancer cells. Therefore, if Sp1-expression is downregulated by RNA interference (RNAi), not only the expression of cancer-related molecules but also glycosylation patterns can be changed in accordance with the altered gene expression of glycosyltransferases, which may lead to the suppression of malignant properties of cancer cells.…”
Section: Abstract Sp1; N-glycan; β4-galactosylation; β4-galactosyltrmentioning
confidence: 99%
“…The cell lysates were prepared from the hGT4-0.3-sensor cells treated with 20 μM U0126 or DMSO for 24 h. Immunoblot analysis using the antibodies against p44/42 MAPK and phosphorylated p44/42 MAPK was conducted, and the band intensity was quantified as the method described previously [8,17].…”
Section: Immunoblot Analysismentioning
confidence: 99%
“…There are seven members of the β4GalT family [7]. Previously, we showed that by regulating the expression level of the β4GalT5 gene, the malignant properties of cancer cells are suppressed [8]. The findings suggest that if the inhibitors for the expression of the β4GalT genes, which relate to the malignant potentials of specific cancer cell types, are discovered, the inhibitors are useful for cancer therapy.…”
Section: Introductionmentioning
confidence: 96%
“…18) In brief, we designed the primer pairs for amplification of the β4GalT4 mRNA 5′-UTR 1, TS27-36 (5′-AGC TCG CCG CGG CCG CCT C-3′) and TS27-38 (5′-ATG AAG CCA CAA AGT GCC AC-3′), while for amplification of the β4GalT4 mRNA 5′-UTR 2, TS27-37 (5′-ACC TTT GAC CTT TCT CCA AA-3′) and TS27-38. The amplification efficiency of each primer pairs was calculated from the slope of the standard curve, and was 123.1 and 122.8% for the amplicons of the β4GalT4 mRNA 5′-UTR 1 and 5′-UTR 2, respectively.…”
Section: Determination Of Transcriptional Start Sitementioning
confidence: 99%